Palynology, depositional environments, and paleoclimatic analysis of OGU-7 well, Niger Delta, Nigeria (Journal of Pure and Applied Sciences (Science Forum), 2026)
Palynological analysis of 100 ditch samples from a section of OGU-7 well, Niger Delta, was carried out to determine the age of the sediment, palynostratigraphic zones, depositional environments, and paleoclimate conditions using data sets from palynology, which well penetrated the paralic Agbada formation. The analyzed samples were from stratigraphic depth intervals of 1,792–9,140 m. Palynological slides were prepared following the standard palynological preparation technique involving hydrochloric (HCl) and hydrofluoric (HF) acids. The palynomorphs yielded 80 species. The section was dated Oligocene–early Miocene due to the occurrence of the diagnostic marker species such as Cicatricosisporites dorogensis, Arecipites exilimuratus, and Echiperiporites estelae. The interval zone of Retitricolporites irregulari and Leiosphaeridia sp.; the taxon range zone of C. dorogensis; and the concurrent range zone of E. estelae and Echiperporites icacinoides were established in line with the International Stratigraphic Guide which could contribute to the harmonization of the biozonation scheme in the Niger Delta Basin. The depositional environment was deduced from the Palynomorph Marine Index values (0% freshwater, 1%–50% brackish, and 51%–100% marine), indicating freshwater to brackish (coastal) environments of deposition for the studied sediment. The paleoecological groupings of the palynomorphs were used to delineate the paleoclimatic signals ranging (wetter to drier phases) from the distribution patterns of Zonocostites ramonae (Rhizophora) and Monoporites annulatus (Poaceae).